E-Government Services and Performance of County Governments in Kenya: The Case of Nairobi City County - Anguche, Cammelyne; Kimani, Hannah; Ndururi, Joseph (European Journal of Business and Strategic Management, 2024)
Purpose: The aim of the study was to examine E-Government Services and Performance of County Governments in Kenya: The Case of Nairobi City County. Methodology: The study adopted a descriptive research design. The target population comprised of 11,603 employees from the Sectors of Mobility and Works, Business and Hustler Opportunities, Boroughs Administration and Personnel, Lands and Build Environment of the county government of Nairobi working at City Hall. The sample size was 387 staff that was calculated using Yamane formula and selected using stratified random sampling method. Piloting was done to establish the reliability and validity of the questionnaire. Quantitative data was analyzed using descriptive and inferential statistics. Descriptive statistics entailed percentages, means and standard deviation. Inferential statistics included Pearson Correlation analysis to determine the nature and strength of the correlation between e-government services and Nairobi City performance. Regression analysis was conducted using multiple regression models to determine the effect of e-government services on performance of Nairobi City County. Data was presented in form of tables. Findings: From the findings, e-government services had a positive and significant influence on the performance of Nairobi City County (F=49.021, P<0.05). Additionally, it was also established that e-parking (b=0.212, p=0.000<0.05), E-Business Licensing (b=0.177, p=0.002<0.05), e-job application ((b=0.232, p=0.000<0.05) and e-land services (b=0.153, p=0.015<0.05) had a positive and significant affect performance of Nairobi City County. The study concluded that e-parking, e-business licensing, e-job application and e-land services are significant determinants of the performance of Nairobi City County. Unique Contribution to Theory, Practice and Policy: The study was guided by Diffusion of Innovation Theory. The study recommended that the county government of Nairobi ought to fully implement e-parking services, e-business licensing services, e-job application services and e-land service to tap its benefits. The study further recommended that the National Government through the ministry of Information, Communications and Digital Economy ought to digitize the delivery of government services to the citizens in all ministries.